Modelling Arctic lower-tropospheric ozone: processes controlling seasonal variations - W. Gong; S. R. Beagley; K. Toyota; H. Skov; J. H. Christensen; A. Lupu; D. Pendlebury; J. Zhang; U. Im; Y. Kanaya; A. Saiz-Lopez; R. Sommariva; et al. (Atmospheric Chemistry and Physics, 2025)
Previous assessments on modelling Arctic tropospheric ozone (O3) have shown that most atmospheric models continue to experience difficulties in simulating tropospheric O3 in the Arctic, particularly in capturing the seasonal variations at coastal sites, primarily attributed to the lack of representation of surface bromine chemistry in the Arctic. In this study, two independent chemical transport models (CTMs), DEHM (Danish Eulerian Hemispheric Model) and GEM-MACH (Global Environmental Multi-scale – Modelling Air quality and Chemistry), were used to simulate Arctic lower-tropospheric O3 for the year 2015 at considerably higher horizontal resolutions (25 and 15 km, respectively) than the large-scale models in the previous assessments. Both models include bromine chemistry but with different mechanistic representations of bromine sources from snow- and ice-covered polar regions: a blowing-snow bromine source mechanism in DEHM and a snowpack bromine source mechanism in GEM-MACH. Model results were compared with a suite of observations in the Arctic, including hourly observations from surface sites and mobile platforms (buoys and ships) and ozonesonde profiles, to evaluate models' ability to simulate Arctic lower-tropospheric O3, particularly in capturing the seasonal variations and the key processes controlling these variations.